Dilemas do Programa de Proteção a Vítimas e Testemunhas Ameaçadas no Brasil = Dilemmas of the Protection of Victims and Threatened Witnesses Program in Brazil - Kuwahara, Shigueo (Política criminal, 2016)
This article is concerned about the potential positioning corresponding to the State and Civil Society, respectively, in the Protection of Victims and Threatened Witnesses Program (PROVITA), looking for arguments about the functionality, origin and the background reasons why citizens' organizations were called upon to assume greater responsibilities for this policy. Such program (from the Federal Law no. 9,807/99) well discharges the State from a task that in principle is shared by it, while guarantor of security rights of citizens through decentralization of protective measures, the involvement of State and nongovernmental institutions in the Deliberative Council of the Program and its association to NGOs committed to the defense of human rights to attend threatened witnesses.